2002
DOI: 10.1542/peds.110.5.e54
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Development During Adolescence in a Biracial Cohort: The NHLBI Growth and Health Study

Abstract: ABSTRACT. Objective. The National Heart, Lung, and Blood Institute Growth and Health Study (NGHS) is a 10-year study to investigate the development of obesity in black and white girls during adolescence and its environmental and psychosocial correlates. The purpose of this report was to examine changes in the annual prevalence rates of overweight and obesity in the NGHS cohort from ages 9 to 19 years.Participants and Setting. A total of 2379 black and white girls, aged 9 to 10 years, were recruited from school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
114
2
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(129 citation statements)
references
References 14 publications
9
114
2
4
Order By: Relevance
“…However, the differences in adiposity levels between PMG and MG subjects are not the same in all ethnic groups. These ethnic dissimilarities in differences in adiposity between MG and PMG are of value in biological anthropological studies of human variation (Richardson et al, 1983;Wang and Bachrach, 1996;Kimm et al, 2001Kimm et al, , 2002Sampei et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the differences in adiposity levels between PMG and MG subjects are not the same in all ethnic groups. These ethnic dissimilarities in differences in adiposity between MG and PMG are of value in biological anthropological studies of human variation (Richardson et al, 1983;Wang and Bachrach, 1996;Kimm et al, 2001Kimm et al, , 2002Sampei et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that ethnic disparity in adiposity evolves during adolescence, although the specific age at which this occurs and the underlying factors are yet to be identified because of the paucity of current longitudinal cohort data among different ethnic groups (Kimm et al, 2001). Thus, ethnic variation in the adiposity difference between PMG and MG girls is of great interest to biological anthropologists investigating human variation (Beunen, et al, 1994;Brown et al, 1996;Kimm et al, 2001Kimm et al, , 2002. India is a large country with vast ethnic heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example in an analysis of 2,379 school children in the USA, Kimm et al showed that the prevalence of both overweight and obesity continued to rise from ages 9-19 years in both black and white females, with very large increases in the late teenage years (Kimm et al 2002). At age nine 30.6 % of black females and 22.4 % of white females were overweight, rising to 39.3 % and 24.1 % respectively at age 16 and 56.9 % and 41.3 % at age 19.…”
Section: When Do Children Become Overweight or Obese?mentioning
confidence: 99%
“…The NHLBI Growth and Health survey was constructed to have equal numbers of African Americans and Whites, and to have approximately equal representation across di¤erent income groups for African Americans and Whites (Kimm et al, 2002). While it is not a nationally representative sample, the strati…cation by race and income are ideal for examining the role that these demographics play in the incidence and persistence of BN.…”
Section: Datamentioning
confidence: 99%